Brian, Psychosis, and the Language of Love. Issue 1 (2nd January 2018) - Naiburg, Suzi
Abstract : Brian grew up in poverty, dropped out of high school at sixteen, and was homeless and psychotic at eighteen. At fifty, he is more than a survivor of poverty, neglect, abuse, and the onset of schizophrenia. When I began to see him for psychotherapy in 1999, I could not have known he would teach me an invaluable lesson about speaking the language of love with a patient. But he did. This is the story of how that happened.